CO2 adsorption on modified carbon coated monolith: effect of surface modification by using alkaline solutions - Hosseini, Soraya; Marahel, Ehsan; Bayesti, Iman; Abbasi, Ali; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw (Elsevier BV, 2015)
A monolithic column was used to study the feasibility of modified carbon-coated monolith for recovery of CO2 from gaseous mixtures (He/CO2) in a variety of operating conditions. Carbon-coated monolith was prepared by dip-coating method and modified by two alkaline solutions, i.e. NH3 and KOH. The surface properties of the carbon-coated monolith were altered by functional groups via KOH and NH3 treatments. The comparative study of CO2 uptake by two different adsorbents, i.e. unmodified and modified carbon-coated monolith, demonstrated that the applied modification process had improved CO2 adsorption. The presence of nitrogen- and oxygen-containing functional groups on the surface of the carbon led to an improved level of microporosity on the synthesized carbon-coated monolith. The physical parameters such as higher surface area, lower pore diameter, and larger micropore volume of modified monoliths indicated direct influence on the adsorbed amount of CO2. In the present study, the Deactivation Model is applied to analyze the breakthrough curves. The adsorption capacity increased with an increase in pressure and concentration, while a reduction of CO2 adsorption capacity was occurred with increase in temperature. Ammonia (NH3) and potassium hydroxide (KOH)-modified carbon-coated monolith showed an increase of approximately 12 and 27% in CO2 adsorption, respectively, as compared to unmodified carbon-coated monolith.